2016
DOI: 10.2196/iproc.6117
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict Depression From the Asymmetry of Electrodermal Activity?

Abstract: IntroductionWhat are the limitations of the methods for depression diagnosis?Though useful for semantic and billing purposes, DSM-based or depression rating scale-based approaches have limited utility for 1) determining subtypes of depression; 2) capturing variations over relatively short time periods (i.e., over the course of a day), and 3) predicting the course of the illness. Therefore we hypothesize that some types of depression may cause patients to have larger electrodermal activity (EDA) on the right th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…EDA has been widely used for various tasks such as seizure detection [44], engagement recognition during social interactions [23], analysis of EDA during sleep [56], or depression prediction based on EDA asymmetry [14].…”
Section: Related Workmentioning
confidence: 99%
“…EDA has been widely used for various tasks such as seizure detection [44], engagement recognition during social interactions [23], analysis of EDA during sleep [56], or depression prediction based on EDA asymmetry [14].…”
Section: Related Workmentioning
confidence: 99%
“…For mental health particularly, wearable computing has been investigated to address depression (Fedor, 2016), stress (Sano & Picard, 2013), (Picard, 2016), anxiety, borderline and bipolar disorder, and schizophrenia (Wang et al, 2016), (Cella et al, 2017), (Torous and Keshavan, 2018 In a search in iTune and Android store, Larsen et al (2016) identified applications for depression, bipolar disorder and suicide. They noticed that few apps were actually clinically relevant (35.3%, 347 out of 982), only nine (2.6%) had clinical effectiveness and only three referred to a published study.…”
Section: Mental Health Applicationsmentioning
confidence: 99%